Desarrollo de un sistema de envasado antimicrobiano para frutos frescos de uchuva (Physalis peruviana L.) (2023)
An active antifungal packaging system combined with modified atmospheres (MAP) was proposed to preserve cape gooseberry. Initially, the antifungal effect of oregano essential oil, cinnamaldehyde, and 2-nonanone in the vapor phase was evaluated in vitro to determine the minimum inhibitory concentration (MIC) for Botrytis cinerea. Next, the better antifungal compound was included inside an active packaging system adsorbed in powdered bentonite. 100 ± 1 g of fruits were introduced in sealed polylactic acid (PLA) packages with a 0.058 mm perforation in the center forming a MAP and stored at 6 °C and 75 % RH determining fungal deterioration and changes in quality properties. From the in vitro tests, it was determined that cinnamaldehyde was the component with the highest antifungal capacity with a MIC of 2,38 µg per cm3 of headspace air. With the active packages combined with MAP, it was possible to obtain up to 42 days of shelf life. © 2023 Elsevier Ltd